CIRCULAR ECONOMY FINANCIAL PRACTICES: FINANCING MODELS FOR SUSTAINABLE BUSINESS INNOVATION - Chevy Herli Sumerli; Fatima Malik; Ahmed Shah (Journal Markcount Finance, 2026)
The transition to a circular economy requires innovative financial practices to support sustainable business models and reduce environmental impact. Traditional financing mechanisms often focus on linear growth, emphasizing short-term profitability over long-term sustainability, which limits the adoption of circular practices. Circular economy financing aims to provide capital, incentives, and risk mitigation strategies that enable businesses to implement resource-efficient, regenerative, and waste-minimizing processes. This study investigates financial models that facilitate circular economy adoption, including green bonds, impact investing, leasing schemes, and public-private partnerships. A qualitative research design was employed, combining systematic literature review with case study analysis of firms implementing circular strategies across manufacturing, energy, and service sectors. Data were analyzed thematically to identify patterns in financing approaches, success factors, and barriers. Findings indicate that tailored financing mechanisms, such as performance-based loans and blended finance models, effectively support circular business innovations by aligning financial incentives with environmental and social outcomes. The study concludes that integrating innovative financial practices into circular economy initiatives can drive sustainable business transformation, enhance competitiveness, and reduce environmental footprint.